The Role of Economic Growth in Moderating the Impact of Energy Consumption on Carbon Emissions in ASEAN-5 - Sahputra, Krishna; Syahnur, Sofyan; Silvia, Vivi (Heca Sentra Analitika, 2025)
The ASEAN-5 countries (Indonesia, Malaysia, the Philippines, Singapore, and Thailand) have experienced rapid economic growth, leading to increased energy consumption and carbon emissions. While economic expansion initially increases emissions, it can also facilitate the adoption of cleaner energy sources. This study investigates the moderating role of economic growth in the impact of energy consumption on carbon emissions using panel data from 2001 to 2022. The Autoregressive Distributed Lag (ARDL) method was employed due to its capacity to analyze both short- and long-term relationships. The results from the ARDL analysis reveal that the consumption of non-renewable energy substantially elevates carbon emissions in both the short and long term. In contrast, the influence of renewable energy consumption on emissions is positive only in the long term. Additionally, non-renewable energy consumption exerts a positive effect on CO2 emissions, which is moderated by both economic growth and the square of economic growth. Conversely, renewable energy consumption contributes negatively to CO2 emissions, similarly moderated by economic growth and its square. These findings correspond with the Environmental Kuznets Curve (EKC) theory, which posits that emissions initially rise alongside economic development, only to subsequently decrease as economies shift towards more sustainable technologies. Therefore, policymakers are advised to implement robust environmental regulations, invest in renewable energy initiatives, and promote sustainable economic practices to achieve long-term carbon reduction goals. Moreover, governments should enforce stricter policies on fossil fuel consumption and raise public awareness of environmental preservation.